Scaffolding's safety in the construction of high rise building / Mohd. Rosmizar Ishak - Ishak, Mohd. Rosmizar (2005)
Malaysia is a fast developing country especially in construction sector. High rise building construction in Malaysia has entering a rapid development stage. Petronas Twin Towers and Kuala Lumpur Tower are the examples of infrastructure development in Malaysia. Many local contractors and local firms involved in this type of construction. In high rise building construction, safety is an important factor that must take in to consideration by contractor. This dissertation focuses on scaffolding's safety especially the workers safety at workplace and safety management of the construction firm.